A primary care survey on the prevalence of lower extremity peripheral obstructive arterial disease among diabetics and its effect on quality of life (QOL) - Abdul Rahman, Mohd Norhisham Azmi; Ab Hamid, Norhayati; Khairul Anuar, Nur Diyana; Md Salleh, Muhammad Syahir Muhaimin; Mahno, Noor Ezmas; Ahmad, Azrin Waheedy; Jamaluddin, A R; Osman, Iskandar Firzada; Othman, Ahmad Faidzal (The Editorial Committee of Annals of Vascular Diseases, 2018)
Background The prevalence of Peripheral Obstructive Arterial Disease (POAD) is significant among diabetics and contributed significantly towards cardiovascular morbidity. Moreover, it substantially reduce the sufferer’s quality of life. Objective This cross-sectional study aims to provide a data on the prevalence of POAD among diabetic population in the primary care in Kuantan and its’ effects on the QoL. Additionally, we examined for any other associated factors that may have contributed towards the development of POAD. Methodology We applied a universal sampling for the purpose of patient selection. POAD is universally defined as ankle-brachial index (ABI) of lower than 0.9. Individuals were assessed on validated Malay version of WHOQOL BREF to assess QoL parameters. P value of <0.05 considered as statistically significant.A favourable opinion was given by Malaysia Ethical Committee (NMRR registration no. 17-137535710). Results The prevalence of POAD among diabetics at Klinik Kesihatan (General Practitioner) Jaya Gading, Kuantan was found to be 20%. It significantly affected the lower levels of education (p = 0.016), older age group (p = 0.02) and lower economic class (p = 0.03). Their QoL adversely affected evidenced by a lower composite scores in all domains calculated using validated Malay version of WHOQOL BREF questionnaires. Conclusion The significant prevalence of POAD among diabetics prompts a greater urgency for early detection to prevent the development of its’ associated morbidity and deterioration of their QoL.